Composicion quimica, actividad insecticida y fungicida de Ocimum micranthum Willd - Murillo, E.=700 1 Viña, A.; Linares, M.
(Es, En)
Ilus., 38 ref.
Keywords: OCIMUM; CONTROL BIOLOGICO; INSECTA; DIPTERA; MUSCA DOMESTICA; FUSARIUM OXYSPORUM; HONGOS; ACEITES ESENCIALES; COMPOSICION QUIMICA; INSECTICIDAS DE ORIGEN VEGETAL; COLOMBIA; OCIMUM MICRANTHUM; ALBAHACA CANELA